Cardiovascular and Mortality Outcomes in the Elderly With Impaired Cardiac and Pulmonary Function: The Cardiovascular Health Study (CHS). Issue 12 (December 2015) - Waheed, Salman; Chaves, Paulo H. M.; Gardin, Julius M.; Cao, Jie Jane
Abstract : Background: Impaired pulmonary function (IPF) and left ventricular systolic dysfunction (LVSD) are prevalent in the elderly and are associated with significant morbidity and mortality. The main objectives of this study were to examine the relative impact and joint association of IPF and LVSD with heart failure, cardiovascular mortality and all‐cause mortality, and their impact on risk classification using a continuous net reclassification index. Methods and Results: We followed 2342 adults without prevalent cardiovascular disease (mean age, 76 years) from the Cardiovascular Health Study for a median of 12.6 years. LVSD was defined as LV ejection fraction <55%. IPF was defined as: forced expiratory volume in 1 second:forced vital capacity <70%, and predicted forced expiratory volume in 1 second <80%. Outcomes included heart failure hospitalization, cardiovascular mortality, all‐cause mortality, and composite outcome. LVSD was detected in 128 subjects (6%), IPF in 441 (19%) and both in 38 (2%). Compared to those without LVSD or IPF, there was a significantly increased cardiovascular risk for groups of LVSD only, IPF only, and LVSD plus IPF, adjusted hazard ratio (95% CI) 2.1 (1.5–3.0), 1.7 (1.4–2.1), and 3.2 (2.0–5.1) for HF; 1.8 (1.2–2.6), 1.4 (1.1–1.8), and 2.8 (1.7–4.7) for cardiovascular mortality; 1.3 (1.0–1.8), 1.7 (1.4–1.9), and 2.1 (1.5–3.0) for all‐cause mortality, and 1.6 (1.3–2.1), 1.7 (1.5–1.9), and 2.4 (1.7–3.3) for composite outcome, respectively. Risk classification improved significantly for all outcomes when IPF was added to the adjusted model with LVSD or LVSD to IPF. Conclusions: While risk of cardiovascular outcomes was the highest among elderly with both LVSD and IPF, risk was comparable between subjects with IPF alone and those with LVSD alone. This observation, combined with improved risk classification by adding IPF to LVSD or LVSD to IPF, underscore the importance of comprehensive heart and lung evaluation in cardiovascular outcome assessment.